Gender differential effects of technical and vocational training: Empirical evidence for Tanzania - Cornel Joseph; Vincent Leyaro (The University of Nottingham, Centre for Research in Economic Development and International Trade (CREDIT), 2019)
This paper investigates the gender differential effect of technical and vocational educational and training (TVET) in Tanzania using data from the 2014 Integrated Labour Force Survey (ILFS). The multinomial logit model results for employment mobility show that TVET training significantly improves males as well as females chances of entering into formal employment while at the same reduces their probability of working in informal, agriculture or being unemployed. The effects are much higher for females relatively to males almost for all categories of education and training. The results further show that though the TVET training increases males as well as females earnings significantly, though the returns to TVET are substantially higher and statistically significant for females than males. The decomposed gender earnings gap using Oaxaca and Blinder (1973) decomposition technique reveal there is a significant gender earning gap in Tanzania, where males tends to earn significantly higher income by 58 percent than females. Clearly, two implications come out here: one, as TVET and general education increases the probability of females more than males to be in the formal employment, investing in girls skills training and education will address the problem of rising youth unemployment and formalize the economy. Two, as returns to TVET and general education is substantially high for females than males, investing in girls' skills skills training and education will address the problem of rising inequality and by extension the higher level of poverty rate in the country.
Keywords: 330; gender; employment mobility; returns; TVET; Tanzania